A comparison of the analgesic effects of butorphanol with those of meloxicam after elective ovariohysterectomy in dogs - Caulkett, Nigel (2003)
This study was designed to compare the analgesic effects of butorphanol with those of meloxicam following ovariohysterectomy. Fifteen dogs were premedicated with 0.05 mg/kg body weight (BW) of acepromazine by intramuscular (IM) injection, plus 0.2 mg/kg BW of meloxicam by subcutaneous (SC) injection. Fifteen dogs were premedicated with 0.05 mg/kg BW of Acepromazine, IM, plus 0.2 mg/kg BW of butorphanol, IM. Anesthesia was induced with thiopental, and dogs were maintained on halothane. All pain measurements were performed by 1 experienced individual, blinded to treatment. Pain scores and visual analogue scales (VAS) were performed at 2, 3, 4, 6, 8, 12, and 24 hours postpremedication. An analgesiometer was used to determine the pressure required to produce an active avoidance response to pressure applied at the incision line. Pain scores, VAS, and analgesiometer scores were analyzed by using a generalized estimating equations method. A significance level of P < 0.05 was considered significant. Animals that received meloxicam demonstrated significantly lower pain scores and VAS than did animals that received butorphanol in the first 12 hours after surgery. Results of this study suggest that meloxicam will produce better postoperative analgesia than will butorphanol. Mucosal bleeding times were performed on cooperative animals in the study group (11 butorphanol, 13 meloxicam). Bleeding times were performed prior to premedication, 6 hours following premedication, and 24 hours after premedication. The 6- and 24-hour readings were compared with baseline bleeding times by using a paired t-test with a Bonferroni correction (a significance level of P < 0.025). Bleeding times did not change significantly over time.